2017
DOI: 10.1016/j.eurpsy.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory, cardio-metabolic and diabetic profiling of chronic schizophrenia

Abstract: IL-2, IL-6, IL-10 and IFN-γ were the most significant SCH-related markers among the measured cytokines in our patient group. Furthermore, significant associations between pro-/anti-inflammatory imbalance and HbA1c as well as cardio-metabolic risk marker (TG/HDL-c) were observed, indicating higher risks of diabetes and cardiovascular diseases among SCH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…Such results are consistent with previous literature 21 that suggests a close relationship between EGF concentrations and psychiatric symptoms as measured using BPRS for the entire patient group. In addition, Balotsev et al 8 showed that EGF serum levels are higher in patients with chronic schizophrenia than those of age-matched normal control subjects. Futamura et al 18 reported significantly decreased serum EGF concentrations in antipsychotic-free patients and in the antipsychotic-naive patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results are consistent with previous literature 21 that suggests a close relationship between EGF concentrations and psychiatric symptoms as measured using BPRS for the entire patient group. In addition, Balotsev et al 8 showed that EGF serum levels are higher in patients with chronic schizophrenia than those of age-matched normal control subjects. Futamura et al 18 reported significantly decreased serum EGF concentrations in antipsychotic-free patients and in the antipsychotic-naive patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators who examined the relationship between peripheral EGF levels and the psychopathology of patients with schizophrenia 8,18,20 yielded conflicting results. A survey conducted by Futamura et al 18 revealed a significant decrease in serum EGF levels in the patient sample (i.e., 4 medication-naive and 45 medicated chronic schizophrenia patients) relative to healthy controls.…”
mentioning
confidence: 99%
“…A postmortem study of 32 individuals with schizophrenia found decreased EGF concentrations in the prefrontal cortex and striatum (21) and elevated concentrations in prefrontal cortex compared to matched controls. Several clinical studies have also examined alterations of serum EGF in schizophrenia patients (21)(22)(23) but have yielded discrepant results. Two studies reported that peripheral EGF levels were substantially higher in patients with schizophrenia compared to healthy controls (22,23), while others reported below-normal serum levels in patients (21,24), and still others found no difference between patients and controls (25,26).…”
Section: Thus We Speculated That Abnormal Expression Of Egf May C O mentioning
confidence: 99%
“…However, similar to positive symptoms, little is known whether improvement in negative symptoms is associated with a reduction of IL‐6 concentration. Low‐grade inflammatory alterations, including changes in IL‐6, were found in peripheral blood samples from chronic schizophrenia patients compared to those from heathy subjects (Balotsev et al, ; Maes, Bosmans, Calabrese, Smith, & Meltzer, ), as well as in post mortem IL‐6 mRNA levels in the dorsolateral prefrontal cortex (Fillman et al, ). Assuming that inflammatory processes also form an important part of schizophrenia pathophysiology in the chronic phase, where the negative symptoms are of crucial importance, we propose that the improvement in negative symptomatology caused by sarcosine may influence inflammatory parameters: for example, by inducing changes in peripheral IL‐6 levels.…”
Section: Introductionmentioning
confidence: 99%